The Role of Blood and Platelets in Atherosclerosis and the Complications of Atherosclerosis - Mustard, J. F; Packham, M. A (Thrombosis and Haemostasis, 1975)
There appear to be at least three ways in which the blood, and particularly the platelets, may contribute to the development of atherosclerosis and its complications :1. In the mechanism causing endothelial injury and the response of the smooth muscle cells to vessel injury.2. Through the formation of persistent mural thrombi which are organized into intimai thickenings.3. Through the formation of thrombi in association with advanced atherosclerosis that may be either (a) mural thrombi which fragment and shower the distal circulation with platelet emboli or (b) occlusive thrombi.